Association of Inhibitory Killer Cell Immunoglobulin-like Receptor Ligands With Higher Plasmodium falciparum Parasite Prevalence. (9th November 2020) - Digitale, Jean C; Callaway, Perri C; Martin, Maureen; Nelson, George; Viard, Mathias; Rek, John; Arinaitwe, Emmanuel; Dorsey, Grant; Kamya, Moses; Carrington, Mary; Rodriguez-Barraquer, Isabel; Feeney, Margaret E
Abstract: Killer cell immunoglobulin-like receptors (KIRs) and their HLA ligands influence the outcome of many infectious diseases. We analyzed the relationship of compound KIR-HLA genotypes with risk of Plasmodium falciparum infection in a longitudinal cohort of 890 Ugandan individuals. We found that presence of HLA-C2 and HLA-Bw4, ligands for inhibitory KIR2DL1 and KIR3DL1, respectively, increased the likelihood of P. falciparum parasitemia in an additive manner. Individuals homozygous for HLA-C2, which mediates strong inhibition via KIR2DL1, had the highest odds of parasitemia, HLA-C1/C2 heterozygotes had intermediate odds, and individuals homozygous for HLA-C1, which mediates weaker inhibition through KIR2DL2/3, had the lowest odds of parasitemia. In addition, higher surface expression of HLA-C, the ligand for inhibitory KIR2DL1/2/3, was associated with a higher likelihood of parasitemia. Together these data indicate that stronger KIR-mediated inhibition confers a higher risk of P. falciparum parasitemia and suggest that KIR-expressing effector cells play a role in mediating antiparasite immunity. Abstract : HLA-C2 and HLA-Bw4, ligands for the inhibitory receptors KIR2DL1 and KIR3DL1, respectively, are associated with an increased risk of Plasmodium falciparum parasitemia in a Ugandan cohort, supporting an important role for the cellular immune response in protection against malaria.